A Review of Embankment Design on Artificial Islands by Dredge Material to Mitigate Flooding - Juliastuti, Juliastuti; Setyandito, Oki; Cahyono, Christian; Suhendra, Andryan; Anda, Martin (Engineering, Technology & Applied Science Research, 2025)
Sedimentation in Lake Tempe, South Sulawesi, Indonesia, has led to significant reductions in the water storage capacity, necessitating dredging efforts and the reuse of Dredged Material (DM) for artificial island construction. This study focuses on designing stable embankments for these islands, which face heightened risks of failure due to the use of low-quality backfill materials and the extreme hydrological conditions. The objective is to determine the required embankment height and assess the effectiveness of geosynthetics and bamboo piles in enhancing slope stability. A comprehensive approach was employed, combining hydrological and geotechnical analyses. The hydrological analysis, based on the 20-year (Q20) and 50-year (Q50) return periods, determined embankment heights of 8.36 meters and 9.2 meters, respectively. The geotechnical analysis using slope stability models revealed that geosynthetic reinforcement significantly outperformed bamboo piles, achieving safety factors well above the critical threshold (1.25) compared to the sub-threshold values for the bamboo piles. These findings underscore the critical role of geosynthetics in mitigating failure risks and enhancing the resilience of embankments constructed with DM.